2022
DOI: 10.1590/1516-4446-2020-1546
|View full text |Cite
|
Sign up to set email alerts
|

Association of FAAH p.Pro129Thr and COMT p.Ala72Ser with schizophrenia and comorbid substance use through next-generation sequencing: an exploratory analysis

Abstract: Objective: Individuals with schizophrenia and substance use disorders have a poor prognosis and increased psychiatric symptoms. The present study aimed to explore the association of 106 genes in individuals with schizophrenia and comorbid substance use through a next-generation sequencing (NGS) analysis and different in silico algorithms. Methods: We included 105 individuals diagnosed with schizophrenia and a family history of schizophrenia, of whom 49 (46.67%) presented comorbid substance use. Using NGS, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The g.-275 T allele frequency in patients with schizophrenia was significantly higher than that in healthy controls in “East Asian” and “Total groups” populations in the database gnomAD ( Supplementary Table S3 ; p = 0.020 and p < 0.001, respectively). It is located in untranslated region, but it has been reported that this variant is associated with negative symptoms of schizophrenia ( Martinez-Magana et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The g.-275 T allele frequency in patients with schizophrenia was significantly higher than that in healthy controls in “East Asian” and “Total groups” populations in the database gnomAD ( Supplementary Table S3 ; p = 0.020 and p < 0.001, respectively). It is located in untranslated region, but it has been reported that this variant is associated with negative symptoms of schizophrenia ( Martinez-Magana et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Monteleone and colleagues suggested that the A allele of the 385C/A (rs324420) FAAH polymorphism may predispose schizophrenic patients treated with antipsychotics to obtain a clinically meaningful weight gain [309]. More recently, an association between the variant FAAH p.Pro129Thr with substance use was found in individuals with schizophrenia [310].…”
Section: Clinical Studiesmentioning
confidence: 99%